Impact of patulin on apoptosis, autophagy, and tumor growth in human malignant mesothelioma and normal mesothelial cells - Akkutlu, Rumeysa; Yuce, Hande; Ozek, Dilan Askin; Berberoglu, Yasemin; Unuvar, Songul (Biomedpress, 2025)
Patulin (PAT) is a mycotoxin produced by certain molds, particularly species of the genera Aspergillus and Penicillium. It is found predominantly in apple-derived products and is associated with both acute and chronic toxicities. Although comprehensive data on the anti-cancer properties of PAT are presently lacking, preliminary evidence suggests that it can influence cancer cells by enhancing cellular apoptosis and inducing cytotoxicity. To evaluate the potential of PAT as a therapeutic approach for malignant mesothelioma, we investigated its effects on the malignant mesothelioma cell line H2452 and the non-malignant mesothelial cell line MeT-5A. Cells were exposed to PAT (1-200 mu M). Cell viability was assessed using the MTS assay, and cell migration was evaluated using the wound-healing assay. Expression levels of genes related to autophagy and apoptosis (SQSTM1, Beclin-1, Atg5, Atg7, Bax, Bcl-2) were measured using RT-PCR. PAT produced a dose-dependent decrease in cell viability and exhibited greater cytotoxicity toward mesothelioma cells than toward healthy cells. The wound-healing assay demonstrated that PAT impeded cellular migration, as evidenced by dysregulated wound closure. In cancer cells, PAT down-regulated Bax, Bcl-2, Beclin-1, and SQSTM1, while up-regulating Atg5 and Atg7. In healthy cells, it reduced Bax, Bcl-2, Beclin-1, SQSTM1, and Atg7, and elevated Atg5. It increased apoptosis in both healthy and cancer cells while modulating autophagy pathways in both cell types, potentially attenuating autophagy in cancer cells and disrupting this process in healthy cells. Our findings indicate that PAT may significantly restrict tumor progression in human mesothelial cancer models.
Keywords: Cancer; H2452; mesothelioma; MeT-5A; mycotoxin; patulin